The Influence of Workplace Spirituality and Organizational Commitment on Organizational Citizenship Behavior in an Islamic Perspective (OCB-IP) with Job Satisfaction as an Intervening Variable among Madrasah Aliyah Teachers in Jonggat District - Fikri Adyantama; Thatok Asmony; Siti Nurmayanti (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the influence of workplace spirituality and organizational commitment on Organizational Citizenship Behavior from in an Islamic Perspective (OCB-IP), with job satisfaction as an intervening variable among teachers at Madrasah Aliyah in Jonggat District, Central Lombok Regency. The research is associative in nature, focusing on causal relationships. Data collection was conducted using a census method with techniques including questionnaires, interviews, observations, and documentation. The population consisted of 191 teachers working at Madrasah Aliyah in Jonggat District, Central Lombok Regency, with a response rate of 178 completed questionnaires, corresponding to a 93.19% return rate. The study employed Structural Equation Modeling (SEM) using SmartPLS for analysis. The results show that workplace spirituality has a significant positive influence on OCB-IP, while organizational commitment has a positive but non-significant influence on OCB-IP. Workplace spirituality has a significant positive influence on job satisfaction, and organizational commitment also positively and significantly influence job satisfaction. Additionally, workplace spirituality significantly positively influences OCB-IP through job satisfaction, and organizational commitment significantly positively influences OCB-IP through job satisfaction. The mediation influence of job satisfaction, as indicated by the Variance Accounted For (VAF) value, is 29% for workplace spirituality and 42% for organizational commitment concerning OCB-IP.